Music For Youth During the Covid 19 Pandemic - Nita Arisanti Yulanda; Suhendri Suhendri; Keti Andriani; Riszky Safitri (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
SARS-CoV-2 virus was found to be targeted cells may be located in the lower respiratory tract, COVID-19 infection can cause mild, moderate to severe symptoms. The main symptoms that appear are fever (> 38oC), cough and difficulty breathing. Vitamin C treatment has an antiviral effect. Clinical trials have shown that administering high doses of vitamin C has a beneficial effect against colds. As a nurse, one of the roles as an extension agent can be carried out in handling Covid-19 patients, namely providing communication, information, and education about health to the community. The role of nurses in providing education to the community is very necessary because it can make people who are given education understand the information conveyed. In this Community Service activity, the focus is on teenagers as one of the preventive efforts against the transmission of the Covid-19 virus through the provision of Health Education on the importance of consuming vitamin C according to the needs of the adolescent body.